Unfulfilled Long-Term Interest Rate Expectations and Changes in Business Fixed Investment - Warner, John C. (American Economic Review, 1978)
The interest elasticity of investment is one of the oldest and most important unresolved issues in monetary theory. It is a key relationship in the most widely accepted theory of how Federal Reserve actions effect the economy.' Unfortunately, there is no consistent empirical verification of this relationship.2 In spite of this lack of empirical support, the theoretical arguments for the interest elasticity of investment are so strong that most experts of monetary theory continue to write books and advise the government on the basis of this relationship. Yet policy exercises are suspect in the absence of some knowledge of the slope of the investment function. The purpose of this article is to use an errorlearning model to investigate the modification of business investment decisions in response to errors in long-term interest rate expectations.